Upaya Meningkatkan Minat Menghafal Al Qur’an dengan Metode Storytelling di Ma’had Tahfiz Manba’ul Huffaz Medan - Idris, Muhammad; Fuad, Muhammad Yusril; Ardhiyah, Ummu; Apriliana; Putri, Elsya Derma; Hidayati, Sri (Al-Wasathiyah: Journal of Islamic Studies, 2025)
The purpose of this study 1) To determine the interest in memorizing the Quran of students before the implementation of the Storytelling Method at Ma'had Tahfiz Manba'ul Huffaz Medan. 2) How is the result of the implementation of efforts to increase students' interest in memorizing the Quran through the Storytelling Method at Ma'had Tahfiz Manba'ul Huffaz Medan. This research uses the type of field research (field research), with the nature of descriptive qualitative research. Data collection techniques are observation, interview and documentation. The research subjects were female students at Ma'had Tahfiz Manba'ul Huffaz Medan. The results of this study indicate that telling stories can increase the interest in memorizing the Quran of students at Ma'had Tahfiz Manba'ul Huffaz Medan. This is evident from the author's interview with students after carrying out the storytelling method at Ma'had Tahfiz Manba'ul Huffaz Medan that their enthusiasm or interest in memorizing the Qur'an is getting better.